2009
DOI: 10.1080/13218710902930325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Questions Used to Elicit Evidence About Abuse from Child Witnesses: Australian Study

Abstract: This study provides one of the first objective evaluations of the performance of a group of Australian police officers when conducting interviews about child abuse. The interviews included 136 videotaped child witness statements, conducted between 2001 and 2007 by police officers from two jurisdictions of Australia. The results indicated many positive aspects of the interviewers' performance, including the use of ground rules at the outset of the interview, commencement of the free-narrative account by seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 22 publications
8
31
0
Order By: Relevance
“…Of course, such training and feedback would be relevant not only for Dutch interviewing practice but also for all countries where child interviewing is not up to par. Indeed, our results align well with interviewing practices in other countries in which the NICHD Protocol is also not applied (e.g., Australia: Powell & Hughes‐Jones, ; Finland: Korkman, Santtila, Westeråker, & Sandnabba, ; New Zealand: Wolfman et al, ; and Norway: Johnson et al, ). Specifically, what is mainly found in these countries is that invitations are also rarely used, suggesting that intensive training and feedback is required to improve interview quality.…”
Section: Discussionsupporting
confidence: 85%
“…Of course, such training and feedback would be relevant not only for Dutch interviewing practice but also for all countries where child interviewing is not up to par. Indeed, our results align well with interviewing practices in other countries in which the NICHD Protocol is also not applied (e.g., Australia: Powell & Hughes‐Jones, ; Finland: Korkman, Santtila, Westeråker, & Sandnabba, ; New Zealand: Wolfman et al, ; and Norway: Johnson et al, ). Specifically, what is mainly found in these countries is that invitations are also rarely used, suggesting that intensive training and feedback is required to improve interview quality.…”
Section: Discussionsupporting
confidence: 85%
“…Rather our results correspond with previous research that has demonstrated a considerable discrepancy between theory and implementation of investigative interviewing protocol guidance (Cederborg, Orbach, Sternberg, & Lamb, 2000;Hershkowitz & Elul, 1999;Powell & Hughes-Scholes, 2009;Thoresen, et al, 2006;Westcott & Kynan, 2006). The only ground rule that was usually included in the rapport stage was the truth and lies discussion.…”
Section: Discussionsupporting
confidence: 80%
“…For example, explaining to children that they should say "I don't know" or "I don't understand" does not necessarily have a positive impact on a child's conversational behaviour (Beuscher & Roebers, 2005;Blades, Waterman, & Gibson, 2003;Ellis, Powell, Thomson, & Jones, 2003;Waterman, Blades, & Spencer, 2004). A further issue is that interviewers' implementation of the ground rules, both in England and Wales and in other countries, is often incomplete and inconsistent (Cederborg, Orbach, Sternberg, & Lamb, 2000;Hershkowitz & Elul, 1999;Powell & Hughes-Scholes, 2009;Thoresen, Lønnum, Melinder, Stridbeck, & Magnussen, 2006;Westcott & Kynan, 2006).…”
mentioning
confidence: 99%
“…However, a comparison of the composition of the interviews in our study with those included in field research shows that the proportions are roughly comparable to those achieved by forensic interviewers following the Protocol (Cyr & Lamb, ; Lamb & Brown, ; Orbach et al ., ; Sternberg, Lamb, Orbach, Esplin, & Mitchell, ). Furthermore, many researchers have shown that interviewing quality and the use of recommended questioning techniques is not associated with years of experience (Powell & Hughes‐Scholes, ; Wolfman et al ., ), nor professional background (Powell, Hughes‐Scholes, Smith, & Sharman, ), meaning that there is no reason to think that our interviews would differ substantively from those in a forensic setting. We saw variations in questioning across and within groups, even though the interviewers were well trained and had access to frequent supervision and fidelity monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer cued invitations were used with CWID-Moderate (but not CWID-Mild) than with the MA children. Consistent with field research showing how difficult interviewers find it to follow research-based recommendations (Korkman, Santtila, & Sandnabba, 2006;Powell & Hughes-Scholes, 2009;Wolfman, Brown, & Jose, 2016a), open invitations were used relatively infrequently irrespective of the children's cognitive or developmental level.…”
Section: Discussionmentioning
confidence: 99%